Grasping Reality : an Interpretation-Realistic Epistemology. - Lenk, Hans (Series on the foundations of natural science and technology., 2003)
Grasping Reality addresses the methodology of a sophisticated realistic approach to scientific as well as everyday recognition by using schemes and interpretative constructs to analyze theories and the practice of recognition from a hypothesis-realistic vantage point. The three main theses are: (1) Any "grasping" of real objects, processes, entities etc. is deeply dependent on scheme interpretations and interpretative constructs - in short, on using schemes and constructs; the same applies to any sophisticated actions encroaching on reality; (2) a sophisticated interpretation-dependent realism.